The UK Breast Cancer in Pregnancy (UKBCiP) Study. Incidence, diagnosis, management and short-term outcomes of breast cancer first diagnosed during pregnancy in the United Kingdom: A population-based descriptive study [version 2; peer review: 2 approved, 1 not approved] - Marian Knight; Andrew Brand; Claudia Hardy; Philip Banfield; Julie Jones (NIHR Open Research)
Background The incidence of breast cancer first arising during pregnancy has been estimated in several countries to be 2.4-7.8/100,000 births, but has not been established in the United Kingdom (UK). We aimed to estimate the incidence of breast cancer diagnosed during pregnancy in the UK and to describe its management and short-term outcomes for mothers and babies. Methods This population-based descriptive study used the UK Obstetric Surveillance System (UKOSS). Cases were prospectively identified through monthly UKOSS mailings to all UK consultant-led maternity units. All cases of breast cancer diagnosed first during pregnancy, between October 1, 2015, and September 30, 2017, were eligible, with 84 confirmed cases analysed. Women with breast cancer diagnosed before pregnancy or with a recurrence were excluded. The primary outcomes were the incidence of breast cancer first diagnosed during pregnancy, maternal mortality, severe maternal morbidity, perinatal mortality, and severe neonatal morbidity. Results The incidence was 5.4/100,000 maternities (95% CI 4.37, 6.70). Nine women (11%) had undergone in vitro fertilisation (IVF), compared with a contemporaneously estimated 2.6% IVF pregnancies in the UK. During pregnancy, 30 women (36%) underwent surgery and 37 (44%) received chemotherapy. Three women had major maternal morbidity during pregnancy. Two women died and two perinatal deaths occurred. Conclusions The incidence of breast cancer arising in pregnancy in the UK is similar to that reported elsewhere. The higher proportion of IVF pregnancies among affected women needs further investigation, as it may not be entirely explained by relatively advanced maternal age. With caveats, management followed that outside pregnancy, but there was considerable variation in practice. Although short-term outcomes were generally good for mothers and babies, a larger prospective study is required. Iatrogenic pre-term delivery and its associated risks to the infant can often be avoided; treatment was administered during pregnancy without evidence of harms to the infant.